Strength in numbers: An isoform variety of homogalacturonan modifying enzymes may contribute to pollen tube fitness - Kamel, Hiba; Geitmann, Anja (Plant physiology (Bethesda), 2023)
Abstract Pectin is a major component of the cell wall in land plants. It plays crucial roles in cell wall assembly, cell growth, shaping, and signaling. The relative abundance of pectin in the cell wall is particularly high in rapidly growing organ regions and cell types. Homogalacturonan (HG), a polymer of 1,4-linked α-D-galacturonic acid, is a major pectin constituent in growing and dividing plant cells. In pollen tubes, an extremely rapidly growing cell type, HG is secreted at and inserted into the apical cell wall and is subject to further modification in muro by HG modifying enzymes (HGMEs). These enzymes, including pectin esterases and depolymerases, have multiple isoforms, some of which are specifically expressed in pollen. Given the importance of pectin chemistry for the fitness of pollen tubes, it is of interest to interrogate the potentially crucial roles these isoforms play in pollen germination and elongation. It is hypothesized that different HGME isoforms, through their action on apoplastic HG, may generate differential methylation and acetylation patterns endowing HG polysaccharides with specific, spatially and temporally varying properties that lead to a fine-tuned pattern of cell wall modification. In addition, these isoforms may be differentially activated and/or inhibited depending on the local conditions that may vary at subcellular resolution. In this Update we review the different HGME isoforms identified in recent years in Arabidopsis thaliana and postulate that the multiplicity of these isoforms may allow for specialized substrate recognition and conditional activation, leading to a sophisticated regulation scheme exemplified in the process that governs the dynamic properties of the cell wall in pollen tube growth.